The ancestors’ masculinities in Genesis - Winkler, Mathias (Journal for the study of the Old Testament, 2021)
In Genesis, many of the male protagonists represent different peoples in the Levant and their relationships among each other. How those ancestors perform as ‘masculine’ men reflects the notion of the masculinity of the peoples descending from them, formulated from an Israelite/Judahite point of view. While the ancestors of Israel and Judah (Seth, Abraham, Isaac, Jacob) perform a certain masculine style, which can be labelled as pious, peaceful, gentle, smart and cultivated, the ancestors of neighbouring peoples (Ham, Lot, Ishmael, Esau) are portrayed as wild or sexually perverted but also aggressive, dominant or hypermasculine. The authors perceive their own people in a historically realistic way; they are no super-men. However, their masculine performance is favoured throughout and even divinely approved.